Percutaneous Coronary Intervention in Stable Coronary Artery Disease - Puspitasari; Ahmad (ARKAVI [Arsip Kardiovaskular Indonesia), 2020)
Coronary heart disease (CHD) is a pathological process characterized by the accumulation of atherosclerotic plaque in the epicardial arteries, both obstructive and non-obstructive. Stable CHD is generally characterized by episodes of reversible myocardial demand or supply mismatches associated with ischemia or hypoxia, which are usually induced by exercise, emotion or other stress, but also occur spontaneously. In recent years, there has been increasing interest in the use of percutaneous coronary intervention (PPI) to treat CHD in complex lesions and in higher risk patients, such as those with comorbidities and poor hemodynamic status. The number of surgical interventions for cardiovascular disease increased between 1980 and 2013. In 2013 there were more than seven times the number of PCI compared to the previous two decades (1993). In patients with chronic coronary syndrome, optimal medical therapy is the key to reducing symptoms, stopping the progression of atherosclerosis, and preventing atherothrombotic events. The two goals of revascularization are symptom relief in patients with angina and or improvement in prognosis. In patients with stable CHD, the initial Fractional flow reserve FFR-guided PCI strategy was associated with lower rates of death, myocardial infarction, or urgent revascularization over 5 years than medical therapy alone. Patients without significant stenosis have haemodynamic significant long-term favorable outcomes with medical therapy alone. Keywords : Coronary heart disease, percutaneous coronary intervention Penyakit jantung koroner (PJK) adalah proses patologis yang ditandai dengan akumulasi plak aterosklerotik di arteri epikardial, baik obstruktif maupun non-obstruktif. PJK stabil umumnya ditandai dengan episode ketidaksesuaian permintaan/pasokan miokard yang reversibel, terkait dengan iskemia atau hipoksia, yang biasanya diinduksi oleh latihan, emosi atau tekanan lain, tetapi mungkin juga terjadi secara spontan. Dalam beberapa tahun terakhir, ada peningkatan minat dalam penggunaan intervensi koroner perkutan (IKP) untuk mengobati PJK pada lesi kompleks dan pasien risiko yang lebih tinggi, seperti mereka yang memiliki komorbiditas dan status hemodinamik yang buruk. Jumlah intervensi bedah untuk penyakit kardiovaskular meningkat antara 1980 dan 2013. Pada 2013 ada lebih dari tujuh kali jumlah IKP dibandingkan dengan dua dekade sebelumnya (1993). Pada pasien dengan sindrom koroner kronis, terapi medis yang optimal adalah kunci untuk mengurangi gejala, menghentikan perkembangan aterosklerosis, dan mencegah kejadian aterothrombotik. Dua tujuan revaskularisasi adalah menghilangkan gejala pada pasien dengan angina dan/atau perbaikan prognosis. Pada pasien dengan PJK stabil, strategi IKP dipandu Fractional flow reserve FFR awal dikaitkan dengan tingkat kematian, infark miokard, atau revaskularisasi mendesak yang lebih rendah dalam kurun waktu 5 tahun dibandingkan terapi medis saja. Pasien tanpa stenosis bermakna secara hemodinamik memiliki hasil jangka panjang yang menguntungkan dengan terapi medis saja. Kata Kunci : Penyakit jantung koroner, intervensi koroner perkutan